PENGARUH BRAND IMAGE TERHADAP BRAND LOYALTY DENGAN BRAND TRUST SEBAGAI VARIABEL INTERVENING PADA PELANGGAN SUPER GEPREK - Chairani Aulia; N. Rachma; Afi Rahmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT This research aims to analyze and understand the influence of Brand Image on Brand Loyalty with Brand Trust as an intervening variable for Super Geprek customers in Malang. The population in this study were customers who had purchased Super Geprek products more than three times at Super Geprek Jalan MT Haryono No.192 Dinoyo-Malang. This research is a type of descriptive research using a quantitative approach and also uses questionnaire research instruments. The research method used is path analysis. The sample in this study was taken using the Slovin formula with accidental sampling technique which is a sampling technique based on chance. A sample of 100 respondents in a population of 3600 consumers was obtained. The results showed that brand image (X1) can influence brand loyalty (Y1) with a value (Sig 0.00), brand loyalty (Y2) can affect brand trust (Y2) with a value (Sig 0,000), brand image (X) has an effect towards brand trust (Y2) with a value (Sig 0.00).Keyword: Brand Image, Brand Loyalty, Brand Trust, Path test, Sobel test.